2019
DOI: 10.1007/978-981-32-9574-2
|View full text |Cite
|
Sign up to set email alerts
|

Fish and Fishery Products Analysis

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Aside from alternative freezing procedures, injecting or dipping antifreeze proteins into meat or fish has shown some efficacy in forcing the production of tiny ice crystals (Mathew et al, 2019;Ustun & Turhan, 2020). Antifreeze proteins have also been found to prevent tiny ice crystals from recrystallizing into larger ice crystals (Eskandari et al, 2020).…”
Section: Freezingmentioning
confidence: 99%
“…Aside from alternative freezing procedures, injecting or dipping antifreeze proteins into meat or fish has shown some efficacy in forcing the production of tiny ice crystals (Mathew et al, 2019;Ustun & Turhan, 2020). Antifreeze proteins have also been found to prevent tiny ice crystals from recrystallizing into larger ice crystals (Eskandari et al, 2020).…”
Section: Freezingmentioning
confidence: 99%
“…Glycosaminoglycan (GAGs) are multifunctional polysaccharides composed of repeating disaccharide units that may change the form of sulfation and epimerization, which determines different functions of protein recognition and biological activities of these compounds [ 72 , 73 ]. Two important groups of complex heteropolysaccharides belonging to the class of GAGs are chondroitin sulfate (CS) and hyaluronic acid (HA).…”
Section: Marine-derived Biologically Active Compoundsmentioning
confidence: 99%
“…Consequently, it is involved in many biological processes at the molecular, cellular, and tissue levels [ 75 , 77 , 78 ]. They play an essential structural role in the composition of extracellular matrix and formation of tissues such as cartilage and bones, abundant in mammals’ connective tissue [ 73 , 79 ]. Some studies have revealed that CS has immunomodulatory and anti-inflammatory properties in several diseases [ 80 , 81 ], highlighting the promising effects of CS reducing symptoms and improving function in osteoarthritis patients, which is one of the consequences of RA in advanced phases [ 82 , 83 ].…”
Section: Marine-derived Biologically Active Compoundsmentioning
confidence: 99%
See 1 more Smart Citation